The Impact of Tai Chi Exercise on Health Care Utilization and Imputed Cost in Residents of Low-Income Senior Housing. (January 2021) - Perloff, Jennifer; Thomas, Cindy Parks; Macklin, Eric; Gagnon, Peggy; Tsai, Timothy; Isaza, Ilean; Wayne, Peter M; Lipsitz, Lewis
Background/Objectives: This study was designed to test the impact of Tai Chi (TC) on healthcare utilization and cost in older adults living in low-income senior housing. We hypothesized that TC would improve overall health enough to reduce the use of emergency department (ED) and inpatient services. Design: Cluster randomized controlled trial with randomization at the housing site level. Setting: Greater Boston, Massachusetts. Participants: The study includes 6 sites with 75 individuals in the TC treatment condition and 6 sites with 67 individuals in the health education control condition. Intervention: Members of the treatment group received up to a year-long intervention with twice weekly, in-person TC exercise sessions along with video-directed exercises that could be done independently at home. The comparison group received monthly, in-person healthy aging education classes (HE). Study recruitment took place between August, 2015 and October, 2017. Key outcomes included acute care utilization (inpatient stays, observation stays and emergency department visits). In addition, the cost of utilization was estimated using the age, sex and race adjusted allowed amount from Medicare claims for a geographically similar population aged ≥ 65. Results: The results suggested a possible reduction in the rate of ED visits in the TC group vs. controls (rate ratio = 0.476, p-value = 0.06), but no findings achieved statistical significance. Adjusted estimates of imputed costs of ED and hospital care were similar between TC and HE, averaging approximately 3, 000 in each group. Conclusion: ED utilization tended to be lower over 6 to 12 months of TC exercises compared to HE in older adults living in low-income housing, although estimated costs of care were similar.